The Influence of Education Level and Occupation of Pregnant Women to the use of Maternal and Child Health (MCH) Handbook: Pengaruh Tingkat Pendidikan dan Pekerjaan Ibu Hamil dengan Pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) - Renny Aditya; Samuel Tobing; Mitfahul Jannah (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective: to investigate the relationship between education level and occupation of pregnant women with MCH handbook utilization at the Pekauman Public Health Center of Banjarmasin in July–August 2018. Methods: the method that was used is analytical observational research with cross-sectional design. The number of research sample is 50 people with systematic random sampling techniques, and data were analyzed by chi-square statistical tests. Results: the majority of respondents were34 pregnant women (68%) with low education level, and36 pregnant women (72%) were unemployed. There were 36 pregnant women (72%) with ineffective MCH handbook utilization. The statistical result between education level of pregnant women with MCH handbook utilization is p-value = 0.005 (p < 0.05) and between occupation of pregnant woman with MCHhandbook utilization is p-value = 0.001 (p <0.05). Conclusion: there a significant relationship of education leveland occupation of pregnant women with MCH handbook utilization at the Pekauman Public Health Center of Banjarmasin in July-August 2018. Keywords: level ofeducation, occupation, MCH handbook Abstrak Tujuan: untuk mengetahui hubungan tingkat pendidikan dan pekerjaan Ibu hamil dengan pemanfaatan buku KIA di Puskesmas Pekauman Banjarmasin Periode Juli–Agustus 2018 Metode: metode yang digunakan adalah observasional analitik dengan desain cross sectional. Besar sampel penelitian adalah 50 orang dengan teknik pengambilan systematic random sampling dan datadianalisis dengan uji statistik chi square Hasil: sebagian besar responden adalah 34 ibu hamil (68%) dengan tingkat pendidikan rendah dan 36 ibu hamil (72%) yang tidak bekerja. Terdapat 36 ibu hamil (72%) dengan pemanfaatan buku KIA yang tidak efektif. Hasil uji statistik antara tingkat pendidikan ibu hamil dengan penggunaan buku KIA adalah p value = 0.005 (p < 0.05) dan antara pekerjaan ibu hamil dengan pemanfaatan buku KIA adalah p value = 0.001 (p < 0.05). Kesimpulan: terdapat hubungan yang bermakana tingkat pendidikan dan pekerjaan ibu hamil dengan pemanfaatan buku KIA di Puskesmas Pekauman Banjarmasin periode Juli–Agustus 2018 Kata kunci: tingkatpendidikan, pekerjaan, buku KIA